Effects of heat and tannic acid treatments on cassava tuber as goat feed - Selvaraju, Renuh (2021)
Cassava (Manihot esculenta Crantz) tuber, which contains high starch content is a good source of dietary energy for animal production. In ruminants, about 75% of the dietary starch fermented rapidly in the rumen. The objective of this thesis was to develop a combination of tannic acid and heat treatment to protect cassava tuber starch from rapid fermentation to allow more by-pass starch to flow into the small intestine to be hydrolysed to glucose for more efficient use by the animals. In brief, this thesis consisted of two studies: the first, to determine the most effective tannic acid x heat treatment combination which can reduce dry matter degradation; and the second, an in vivo trial to test the efficacy of feeding the treated cassava tuber on production, rumen fermentation parameters and nutrient digestibility. In the first study, a 4 tannic acid levels x two temperatures factorial experiment, giving a total of 8 treatments: T60C (control), T60L T60M, T60H (0, 2.5, 5 and 7.5% TA treated at 60°C) and T120C, T120L, T120M, T120H (0, 2.5, 5 and 7.5% TA treated at 120°C), was used. Degradation characteristics of the treatment samples were tested using in vitro gas production and in sacco nylon bag techniques. Both procedures showed that cassava tuber treated with T120H was most effective to reduce its fermentation rate. Thus, T120H was selected to treat cassava tuber in the follow-up feeding trial. In the feeding trial, 12 male Boer crossbred goats of 7-9 months old were randomly allocated into two dietary groups (control and treated). Goats in the control group was offered mixed diet consisted of 30% roughages and 70% concentrate (containing 30% cassava tuber), while the treated group was offered the same diet except that the cassava tuber was treated with the procedure of T120H. There were no differences in the average daily gain and feed conversion ratio between the two groups. Dietary treatment did not alter rumen fermentation parameters, except it reduced (P<0.05) acetate production in treated group. The dietary treatments also did not affect rumen microbial population except the goats in the treated group had lower methanogen population (P<0.05). Dry matter, crude protein and starch digestibility were not affected by dietary treatments; however, the digestible starch intake of the treated group was lower (P<0.05) than the control. This could partly attribute to the binding of tannic acid with the starch to inhibit the total conversion of the starch to the respective reducing sugars during the analytical procedure in determining the starch content of diets. It is concluded that treating cassava tuber with 7.5% tannic acid at 120°C significantly reduced degradation rate as evident by the 23% reduction in the effective degradation rate (ED, k=0.05) of cassava tuber in the in sacco study. The feeding of the treated cassava tuber did not improve growth performance in goats and the estimated digestible starch intake of goats in the treated group was drastically lower than that in the control group. The reason behind the lower digestible starch intake needs further investigation.